Application of Taguchi methods in the optimization of cutting parameters for surface finish and hole diameter accuracy in dry drilling processes - KURT, MUSTAFA; KAYNAK, YUSUF (SPRINGER LONDON LTD, 2009)
The aim of the work reported here was to utilize Taguchi methods to optimize surface finish and hole diameter accuracy in the dry drilling of Al 2024 alloy. The parameters of hole quality are analyzed under varying cutting speeds (30, 45, and 60 m/min), feed rates (0.15, 0.20, and 0.25 mm/rev), depths of drilling (15 and 25 mm), and different drilling tools (uncoated and TiN- and TiAlN-coated) with a 118A degrees point angle. This study included dry drilling with HSS twist drills. The settings of the drilling parameters were determined by using Taguchi's experimental design method. Orthogonal arrays of Taguchi, the signal-to-noise (S/N) ratio, the analysis of variance (ANOVA), and regression analyses are employed to find the optimal levels and to analyze the effect of the drilling parameters on surface finish and hole diameter accuracy values. Confirmation tests with the optimal levels of machining parameters are carried out in order to illustrate the effectiveness of the Taguchi optimization method. The validity of Taguchi's approach to process optimization is well established.
Keywords: Taguchi optimization method; Analysis of variance (ANOVA); Drilling; Surface finish; Hole diameter accuracy; ALUMINUM-ALLOYS; QUALITY; WEAR; PERFORMANCE; COATINGS